Análisis de los determinantes del cambio de la demanda de energía eléctrica en la ciudad de Neuquén - Domeett, Griselda (2015)
The electrical energy is a basic input of high diffusion, derived from its capacity to satisfy all type of necessities. It shows that seasonal alterations in the consumptions are motivated by the level of economic activity, climatic changes and demographic dynamics. Since this is an essential good that cannot be stored, it determines the configuration, planning, operation and organization of the electrical energy systems. Its particular feature is forced to perform a multidimensional coverage: technological, economic, political, legal and environmental. The analysis of the factors that determine the levels and structures of the electric energy consumption it allows to identify the supplying problems, and the actions and policies that promote the sustainable usage of the service.Accordingly, the current work tries to make a preliminary analysis of these changes in the capital city of Neuquén, since the 90s until recent years. In order to do this, information from the Population Census, Provincial Registers, Household Surveys, Consumption and Invoicing sector, has been used.